Close Association between parathyroid hormone and left ventricular function and structure in end-stage renal failure patients under maintenance hemodialysis - Nasri, Hamid; Baradaran, Azar (Journal of Ayub Medical College Abbottabad, 2004)
Background: Cardiovascular risk factors are a significant burden in end-stage renal disease patients under hemodialysis and are the leading cause of death among these patients. The influence of parathyroid hormone (PTH) on myocardial function as a toxin of uremia is under more attention and evaluation becaue of growing evidence showing that the effects of PTH on cardiac function may be the most serious consequence of secondary hyperparathroism in renal failure.In this study we determined role of excess PTH in the development of left ventricilar (LV) hypertrophy as well as LV ejection fraction in patients with end-stage renal disease under regular hemodialysis. Methods: This study is cross-sectional that was done on patients with end-stage renal disease (ESRD) undergoing maintenance hemodialysis treatment. For patients, Calcium, Phosphorus, Alkaline phosphatase and Intact PTH (iPTH) were measured. Hypertensive patients were stratified into stages one to three. Ecocadiographies for LV hypertrophy and ejection fraction (%) were done and patients stratified into normal ,mild, moderate and severe LV hypertrophy. Results: The total patients were 73(F=28 M=45), consisting of 58 non diabetic hemodialysis patients (F=22 M=36), and 15diabetic hemodialysis patients (F=6 M=9).The mean age was 46.5±16 years. The time on hemodialysis was 21.5±23.5months. The LV ejection fraction (EF%) were 51±8 percent. ’˜iPTH’ of patients was 309±349 Pg/ml. ’˜iPTH’ of diabetic and nondiabetic groups was 234±265 pg/ml and 329±368 pg/ml respectively. Serum alkaline phosphatase was 413±348 IU/L. Serum alkaline phosphatase of diabetic and nondiabetic groups were 295±179 IU/L and 443±375 IU/l respectively. Serum albumin was 4±0.75 g/dl. Serum albumin of diabetic and nondiabetic groups was 3.6±0.7 g/dl and 4.2±0.7 g/dl respectively. Significant inverse correlation of serum ALP with percent of LV ejection fracction and marginal positive correlation of serum ALP with LVH and also marginal correlation of serum iPTH with LVH were seen. Also significant inverse correlation between serum iPTH with percent of LV ejection fraction in non diabetic heart patients was observed. Conclusions: Adverse effects of secondary hyperparathyroidism on LV function and structure in this study show the role of excess PTH in the development of left ventricilar (LV) hypertrophy as well as low LV ejection fraction in patients with end-stage renal disease under hemodialysis which needs more attention to control of secondary hyperparathyroidism to reduce the risk of cardiovascular morbidity and mortality in dialysis patients . Keywords: Hemodialysis, Left ventricular hypertrophy, Ejection fraction ,Secondary hyperparathyroidism